City of Hamilton Signs Climate Change Emergency Declaration, Reduces Energy Consumption in Water System. Issue 11 (3rd November 2020) - Sucharda, Peter; Gimson, Mark
Key Takeaways: The City of Hamilton, Ont., signed a climate change emergency declaration, with the goal of net zero carbon emissions by 2050. As part this plan, Hamilton Water is seeking a more efficient water distribution system that reduces water loss and electricity consumption. A pilot project demonstrated that Hamilton could achieve significant energy savings and reduce water loss using anti‐stagnation valve technology in its pressure district zones. Hamilton aims to expand the installation of anti‐stagnation valves, which is estimated to result in substantial annual cost savings.